PERCEPTIONS OF FINAL-YEAR MBBS STUDENTS TOWARD TRADITIONAL CLINICAL TEACHING VERSUS ACTIVE PARTICIPATION IN CLINICAL EDUCATION - PRABHU DAYAL; DINESH SOLANKY; PRAVEEN KUMAR GARG; ANKIT AWASTHI (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: The objective of this study was to gain the perspectives of medical students on two different teaching approaches in clinical education. Methods: This research was designed as an educational interventional crossover study to compare two clinical teaching methods and assess their impact on students’ educational experiences. Conducted at Government Medical College, Pali, the study aimed to evaluate how active participation in clinical rounds versus traditional clinical teaching affects MBBS final-year students’ perceptions and learning outcomes. Results: Active participatory teaching is more effective in promoting student engagement and active learning compared to traditional clinical teaching. Conclusion: Active participation in clinical rounds significantly enriches students’ educational experience and prepares them for practical, patient-centered medical practice.